2009
DOI: 10.1097/meg.0b013e328304e0cc
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax as a presenting feature of granulomatous disease of the lung in a patient with Crohnʼs disease

Abstract: Pulmonary disease and abnormalities of pulmonary function testing have been described in patients with Crohn's disease. The case of a 25-year-old female presenting with pneumothorax as a complication of Crohn's-related granulomatous lung disease is described here. The patient presented with symptoms of dyspnoea and chest pain, a chest radiograph revealed a pneumothorax on the right side. This pneumothorax did not resolve with intercostal tube drainage. Video-assisted thoracoscopy was performed at which small b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Good responses to steroids have been reported in all cases of pleuritis or pleuropericarditis. Pneumothorax is a rare complication, and was described in a patient suffering from CD-related granulomatous lung disease [ 90 ]. An air-leak syndrome (pneumothorax, pneumomediastinum and subcutaneous emphysema) associated with organizing pneumonia pattern was described as an unusual presentation of UC-related bronchopulmonary involvement [ 91 ].…”
Section: Other Forms Of Respiratory Involvementmentioning
confidence: 99%
“…Good responses to steroids have been reported in all cases of pleuritis or pleuropericarditis. Pneumothorax is a rare complication, and was described in a patient suffering from CD-related granulomatous lung disease [ 90 ]. An air-leak syndrome (pneumothorax, pneumomediastinum and subcutaneous emphysema) associated with organizing pneumonia pattern was described as an unusual presentation of UC-related bronchopulmonary involvement [ 91 ].…”
Section: Other Forms Of Respiratory Involvementmentioning
confidence: 99%
“…Such reports with sequential sarcoidosis–Crohn’s-associated forms are rare. This is the case of a pneumothorax arising from a peripheral parenchymal necrotic granulomatous lesion, in which simultaneous Crohn’s disease was identified by colonoscopy [ 38 ]. Montembault et al [ 39 ] also reported the case of a woman in whom the first episode of Crohn’s disease was accompanied by sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%